2020
DOI: 10.1016/j.ydbio.2020.05.009
|View full text |Cite
|
Sign up to set email alerts
|

FGF signaling promotes myoblast proliferation through activation of wingless signaling

Abstract: Indirect flight muscles (IFMs) are the largest muscles in Drosophila and are made up of hundreds of myonuclei. The generation of these giant muscles requires a large pool of wing disc associated adult muscle precursors (AMPs), however the factors that control proliferation to form this myoblast pool are incompletely known. Here, we examine the role of fibroblast growth factor (FGF) signaling in the proliferation of wing disc associated myoblasts. We find that the components of FGF signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 55 publications
(66 reference statements)
0
24
0
Order By: Relevance
“…Thus, the localized expression and level of Ths and Pyr secreted by epithelial cells in the notum could provide sufficient trophic support to generate the appropriate number of AMPs during normal development. While this work was in preparation, another group independently showed that the ths-Gal4 line is expressed in the notum epithelium and that reducing ths function reduces AMP numbers ( Vishal et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the localized expression and level of Ths and Pyr secreted by epithelial cells in the notum could provide sufficient trophic support to generate the appropriate number of AMPs during normal development. While this work was in preparation, another group independently showed that the ths-Gal4 line is expressed in the notum epithelium and that reducing ths function reduces AMP numbers ( Vishal et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies found that FGF10 emanated from the prospective limb mesoderm in birds to serve as an endogenous initiator for limb bud formation, which is associated with the loss of ight in emu (Dromaius novaehollandiae) [43,44]. In drosophila, components of FGF signaling are expressed in myoblasts, a series of experiments show that FGF is a key factor of the development of ight muscle in drosophila [45,46]. Therefore, FGF14 very likely plays an important role in loss of ight in domesticated ducks.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, the wing disc epithelium releases FGF, which acts through Heartless (Htl) to activate the Wingless pathway. 79 This activation is required to achieve normal levels of AMP proliferation, and constitutively active Htl receptors result in an enlarged myoblast pool, at least in the wing disc.…”
Section: Metamorphosis In Insect Muscle 333mentioning
confidence: 99%
“…Previous work in this field has already demonstrated that transfection with a constitutively active form of the FGF receptor Heartless is known to increase AMP proliferation in vivo, and transfection with the Caenorhabditis elegans fusogenic protein Eff-1 can initiate fusion in a nonfusing cell line, especially with overexpression of Sns. 79,84 In addition, it might be possible to define factors controlling the identities of specific IPs and to use these cells to direct the eventual fate of the muscles as they develop in vitro.…”
Section: Strategies For Engineering Insect Musclementioning
confidence: 99%